Keterampilan Komputer Terhadap Kemandirian Remaja Disabilitas Netra Kelas VIII Di SLB-A Pembina Tingkat Nasional Jakarta - Alfrida Hermawati; Ati Kusmawati (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
In 2020, the Central Statistics Agency (BPS) revealed that current data shows that the number of people with disabilities in Indonesia reached 22.5 million people. Meanwhile, referring to estimates from the Indonesian Ministry of Health in 2017, the number of visually impaired people in Indonesia was 1.5% of the entire population. Teenagers with visual disabilities have visual impairments so they experience limitations in various experiences, the ability to encounter objects and interact with their environment. One way to increase the independence of blind teenagers is with a self-development program through computer information implemented by schools. SLB-A National Level Coach Jakarta. This research aims to describe a self-development program through computer information for the independence of class VIII blind teenagers at SLB-A Pembina National Level in Jakarta. This research uses descriptive qualitative methods. Data collection was carried out by means of observation, interviews and documentation. Determining informants using snowboll sampling. The results of this research indicate that the self-development program through computer skills implemented at the Jakarta National Level Pembina SLB-A plays a role in increasing students' social, emotional and intellectual independence. Then, at the SMPLB level, students are more interested in computer skills which are relevant at this time in the era of technological development.